THE NAIRIT POLYCHLOROPREN ELECTRORESISTANCE CHANGE DEPENDING ON THE FILLING SUBSTANCE, TEMPERATURE AND AGEING - Martirosyan, A. H.; Aghabekyan, V. N.; Grigoryan, P. A. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2003)
In the present work the experiments on obtaining polychloropren Nairit films with different electroconductive fillers were made and their electroresistance is investigated. The character of the electroresistance change depending on the type of conductor filler is revealed. The electroresistance changes of these films are determined depending on the temperature and ageing.